INTERAKSI NOTARIS DAN DINAMIKA HUKUM AGRARIA DALAM TRANSAKSI TANAH - Noor, Aslan; Rusaedi, Attansya Rafli; Izzani, Muhammad Hasbi Rizqan; Wildan, Wildan (LPPM STIH Putri Maharaja, 2024)
A notary can authenticate deeds and other legal responsibilities as a public official. With the enactment of UUJN no. 30 of 2004, discussions arose regarding the notary's jurisdiction in drafting deeds on land matters. This study aims to assess the efficacy of notaries' roles and duties in facilitating land registration processes in Indonesia, utilizing normative juridical methods to inventory, review, analyze, and comprehend legal norms governing notarial functions. It elucidates that, according to PP No. 24 of 1997, the individual assisting the Head of the Land Office is referred to as PPAT, with no mention of notaries as officials authorized to draft deeds for land registration. Nonetheless, certain deeds require notarial authentication when the PPAT lacks authority, serving as an essential component for land registration. Notaries' pivotal role and responsibility in land registration activities lie in the function of the deeds they produce, serving as evidence of legal actions and foundational documents for land registration at land offices. Consequently, the absence of notarial deeds could impede land registration data maintenance, as they are indispensable prerequisites for land registration processes.